Validating The ISO 9000 Construct of Measurement Instrument Through Application of RASCH Model - Yusuff, Rushami Zein; Abas, Zakaria; Abd Aziz, Azrilah; Masodi, Mohd Saidfudin; Saad, Rohaizah (The Asian Journal of Technology Management (AJTM), 2011)
There are numerous researches conducted on the issues related to ISO 9001 quality management system. Among the issue is the impact of the ISO 9001 quality management system implementation on the performance of the organization. However the findings from the research appeared as inconclusive. Few literature suggest that the inconclusive result may due to the level of ISO 9000 implementation therefore further research is required. Generally the data collected for these types of researches are through mailed questionnaires and analyzed it using SPSS and SEM. In line with that this study also developed questionnaires correspond to a 5 point Likert to assess the implementation of ISO 9000 in the organization. As a result 231 items are identified within five dimensions. The five dimensions are derived from ISO 9001 and ISO 9004 quality management standards requirement and guidelines. Among the dimensions are management responsibility, resource management, product realization, measurement improvement and innovation and organizational performance. The questionnaires are sent to 78 automotive based companies located in the Northern region of Peninsular Malaysia. 19 questionnaires were returned and used as pilot test to validate and calibrate the instrument. The responds from the organization are tabulated and run in WinSteps software for the purpose of validating and calibrating the instrument by implementing the Rasch ‘quality control’ and reduction of items. Not all the outfit items are removed from the instruments, Rasch Model did provide room for the researcher to make decision either to remove or not those outfit items. In this study those outfit items need to be corrected in order to ensure that the instrument is reliable and fit to measure the performance of the organization. As a result 68 items are removed from the questionnaires.Keyword: rasch model, ISO 9001, quality control and items reduction.